EVALUASI STREET FURNITURE LAMPU JALAN DI KORIDOR KAWASAN MALIOBORO, YOGYAKARTA - Dwi Sisilia Saputri, Retna Hidayah (Universitas Negeri Yogyakarta, 2014)
This study aims to evaluate street furniture street lamp in the Malioboro area throughan aesthetic stand point, placement and lighting quality. Factors that make Malioboro be valuedand made a deep impression in the hearts of the people, the street furniture street lamp functionadds to the beauty of Malioboro at night. The existence of street lights should be in accordancewith the purpose of planning, so as to provide safety, comfort and strengthen the character ofan area. This study used survey method. Data collected through the measurement results, anddirect observation in the Malioboro area. The results showed that: (1) the design of lamppostshave a design detail, aesthetic, and gives the impression and feel of high-value works of art; (2)the color of white light is less to show the impression of beauty and reduce the region's identity;(3) Placement of signage looks crowded, disturbing viewpoint and identity elements of streetlights; (4) the placement of the distance between the lights are still very far apart, yet give astrong character to the aesthetics; (5) lighting quality meets the standard of lighting levels, butshould consider the main purpose of planning.Keywords: Aesthetics, identity, light path.